CARACTERIZAÇÃO DA MATÉRIA ORGÂNICA HUMIFICADA DE UM LATOSSOLO VERMELHO DISTRÓFICO ATRAVÉS DA ESPECTROSCOPIA DE FLUORESCÊNCIA INDUZIDA POR LASER - Favoretto, Célia Mara (2007)
Soil organic matter is essential for its quality and productivity, being its process of humification affected by the climate, soil type and soil management, resulting in the formation of fluorescent groups that can be measured through Laser- Induced Fluorescence Spectroscopy, a recent technique that has been showing efficient for analysis of whole soil, that is, soil without any physical or chemical treatment. This technique was used to determine the humification degree of the Organic Matter of a whole soil, as well as the physical fraction for particle size. It can also be used to relate the results of the quantification of the humification organic matter with the depth of the soil and planting systems. On the surface of the soil, No-Tillage got the smallest humification in comparison with the conventional tillage and the reduced tillage, whereas the fractions of the superficial layer of the soil (0-20 cm), indicated larger humification in the fraction (20-53) and the smallest in the fraction (2 ), in all treatments.